Management and outcomes of a COVID‐19 outbreak in a nursing home with predominantly Black residents. Issue 5 (24th March 2021) - Beiting, Kimberly J.; Huisingh‐Scheetz, Megan; Walker, Jacob; Graupner, Jeffrey; Martinchek, Michelle; Thompson, Katherine; Levine, Stacie; Gleason, Lauren J.
Abstract: Background/Objectives: Few studies present clinical management approaches and outcomes of coronavirus disease 2019 (COVID‐19) outbreaks in skilled nursing facilities (SNFs). We describe outcomes of a clinical management pathway for a large COVID‐19 outbreak in an urban SNF with predominantly racial minority (>90% black), medically complex, older residents. Design: Single‐center, retrospective, and observational cohort study (March 1, 2020–May 31, 2020). Setting and Participants: All subacute and long‐term care residents at an urban SNF between March 1, 2020 and May 31, 2020 (Chicago, IL). Intervention: A multicomponent management pathway was developed to manage a large COVID‐19 outbreak in an SNF. Measurements: Chart review was used to extract demographics, comorbidities, symptoms, lab results, and clinical outcomes over 12 weeks, which were summarized and compared between residents with and without COVID‐19. Results: A multicomponent clinical management pathway was used to care for residents with COVID‐19, which included frequent scheduled clinical and laboratory evaluation, use of intravenous fluids, supplemental oxygen, antibiotics when indicated, and goals‐of‐care discussions. Of the 204 residents, 172 (84.3%) tested positive for SARS‐CoV‐2 during the 3‐month period, with 50.5% symptomatic, 9.3% presymptomatic, and 24.5% asymptomatic, with a 30‐day mortality rate of 15.7%. Predominant symptoms were low‐grade fever >99 °F, anorexia, delirium, and fatigue. While in the facility, approximately one‐quarter of residents experienced hypernatremia [Na > 145 mEq/L] (24.5%), acute kidney injury [Cr > 0.03 mg/dL or 1.5× baseline] (29.7%), or leukopenia [WBC < 4.8 1000/mm 3 ] (39.4%). Conclusion: We present the first available clinical strategy guiding the medical management of a COVID‐19 syndrome in an urban SNF, caring for largely black residents, which may lead to improved mortality.